The Formulation of the Dependent Variable in the Wage Equation - Black, S. W.; Kelejian, H. H. (Review of Economic Studies, 1972)
S. W. Black, H. H. Kelejian; The Formulation of the Dependent Variable in the Wage Equation1, The Review of Economic Studies, Volume 39, Issue 1, 1 January 1972